Efektivitas Sistem E-Berpadu Dalam Perkara Pidana Sebagai Upaya Mewujudkan Peradilan Cepat - Candra, Ade; Danil, Elwi; Elvandari, Siska; Robensyah, Andes (Universitas Ekasakti, 2024)
This research aims to see the effectiveness of the E-Berpadu system which was launched by the Supreme Court through Perma Number 4 of 2020 and refined with Perma 8 of 2022. The E-Berpadu system is an application used to simplify processes in the criminal justice system. This application emerged as an initiative during the Covid-19 pandemic where everyone was encouraged to carry out activities from home. This is why this application with the E-Berpadu system is here to make things easier for the public and law enforcement officers in the criminal justice system. This research uses a normative juridical legal approach with analytical descriptive methods. The results of this research are that through the E-Berpadu system, it has provided convenience to the public and law enforcement officers in the criminal justice system. The E-Berpadu system makes it easy for law enforcement officers to access it only through their respective offices via the application.